Feedback solutions for low crosstalk in dense arrays of high-Tc SQUIDs for on-scalp MEG. (18th April 2017) - Ruffieux, S; Xie, M; Chukharkin, M; Pfeiffer, C; Kalabukhov, A; Winkler, D; Schneiderman, J F
Abstract: Magnetoencephalography (MEG) systems based on a dense array of high critical temperature (high- T c ) superconducting quantum interference devices (SQUIDs) can theoretically outperform a state-of-the-art MEG system. On the way towards building such a multichannel system, we evaluate feedback methods suitable for use in dense high- T c SQUID arrays where the sensors are in very close proximity to the head (on-scalp MEG). We test on-chip superconducting coils and direct injection of the feedback current into the SQUID loop as alternatives to the wire-wound copper coils commonly used in single-channel high- T c SQUID-based MEG systems. For the evaluation, we have performed coupling, noise, and crosstalk measurements. We conclude that direct injection is the optimal solution for dense on-scalp MEG as it gives crosstalk below 0.5% even between SQUIDs whose pickup loops are within 0.8 mm of one another. Further, this solution provides sufficient flux coupling without adding additional noise. Finally, it does not compromise the standoff distance, which is important for on-scalp MEG.